The Artistic Characteristics and Cultural Inheritance of Hunan Baling Opera Run Cavity - Gao, Xia; Jirajarupat, Phakamas; Zhao, Shufeng (Journal of Dhamma for Life, 2024)
This study discusses in depth the artistic characteristics of Hunan Baling Opera Run Cavity and its cultural inheritance. The research objectives of this paper are: 1) to sort out the historical origin of Balinese Opera Run Cavity; 2) to analyse the artistic characteristics of Balinese Opera Run Cavity; 3) to put forward the corresponding inheritance strategy and innovation path. This paper adopts the field survey method and literature research method to sort out the historical origin of Baling Opera and its formation process; secondly, it analyses the phonological characteristics, performance techniques and musical features of Runqiang through the music analysis method and the case study method; finally, the paper discusses the challenges faced by Baling Opera Runqiang in the modern society and proposes a strategy of innovation and development on the basis of the protection of the traditional culture to provide a theoretical basis and practical development of the long term inheritance and development of Baling Opera Runqiang. Finally, the article discusses the challenges faced by Baling Opera Runqiang in the modern society, and proposes strategies to achieve innovative development based on the protection of traditional culture, providing theoretical basis and practical guidance for the long-term inheritance and development of Baling Opera Runqiang.